Pengembangan Media Puzzle Untuk Pembelajaran Akuntansi di SMK Nusatama Padang - Melati Yustantia; Marwan Marwan (Universitas Negeri Padang, 2023)
This study aims to: 1) Develop a puzzle media model for Accounting learning at SMK Nusatama Padang, 2) Test the feasibility of a puzzle media model for learning Accounting at SMK Nusatama Padang, 3) Measure the practicality of puzzle media for learning Accounting at SMK Nusatama Padang. This type of research is research and development with the ADDIE model. Data collection uses a validation sheet consisting of material experts, media experts, and linguists. The Response questionnaire consisted of teachers and students. The test subjects in this study were 34 students of class XI AK 1 SMK Nusatama Padang. The results showed that first, the feasibility level of the developed media was based on the assessment: 1) Material experts showed an average of 4.36 in the very appropriate category, 2) Media experts showed an average of 4.44 in the very feasible category. Second, the results of the questionnaire show that the learning media has been very practical with an average of 4.27 on the teacher's response and 4.66 on the student's response. Thus, it can be concluded that the puzzled media for accounting learning at SMK Nusatama Padang has been declared feasible and practical to be in learning.